Praca jako obowiązek a praca jako źródło satysfakcji. Studium historyczne roli i znaczenia pracy w dziejach Polski (po 1945 roku) - Kamosiński, Sławomir (Annales. Etyka w Życiu Gospodarczym, 2016)
The paper presents an analysis of the ethical, political and economic aspects of humanwork within two Polish historical periods – the years of the People’s Republicof Poland and after 1989. The starting point for the analysis was the assumption thatevery time period, each age, leaves a mark on man’s work.Analysis of the People's Republic of Poland period gives an opportunity toconsider human work understood as a duty and right of every human guaranteed bythe Constitution of 1952. Questioning the principles ruling the labour market by theideologists of the People’s Republic of Poland and, as a consequence, the politicizationof labour, resulted in the collapse of the work ethic. Work, as it was at thattime a commonly available good, lost its value, regarded as the source of life satisfaction,and thus became ridiculed.After 1989, in relation to the de-politicization of the Polish labour market, theemployee became active in searching for a job. The phenomenon of unemploymentresulted in competition on the labour market and the employer was thus given theopportunity to freely select a group of employees. As a result, the employer becamea distributor of a ‘rare commodity.’ That, in turn, led to the situation where the approachof employers towards employees turned into the employer's diktat. It is theemployer who determines the conditions of employment, standards of work andplace of work. A lack of alternative that many employees face often makes themaccept the dictated conditions of work. What is more, in Poland we deal with theinsufficiently developed participation of employees in managing the enterprises,which is an effect of breaking off the bilateral dependency of employee and employer.